Analysis of Structural Equation Modeling as a Measuring Tool for Educational Management Research - Qanita, Afiana; Faris Fadhlillah, Muhammad; Supriyana, Andika (Pandawan, 2018)
In management education and psychology there are certain concepts that cannot bewell defined and then various discussions arise about the true meaning of the concept.Concepts such as management intelligence, personality, attitudes, interests, ambitions, socialprejudice and social status are hypothetical constructs that are not available in operationalmethods that can directly measure them. Concepts such as intelligence, personality, attitudes,interests, ambitions, social prejudice, social status are hypothetical constructs that are notavailable operational methods that can directly measure them. This study aims to determine thebackground of the use of Structural Equation Modeling (SEM), understanding SEM, basicconcepts of SEM: constructs, manifest variables, validity, reliability, factor analysis, polycoriccorrelation, causal relationships, LISREL: Linear Structural Relationship, SEM procedures :definition of variance and covariance, model specifications, model identification, modelestimation, model formation, model compatibility test, model specification, LISREL programoutput. Symbols in SEM and SEM mathematical equations. The method used during this studytook place, namely using a literature study method which functions so that in research,researchers continue to add insight.